The Cherokee Perspective Written by Eastern Cherokees - French, Laurence; Hornbuckle, Jim (Appalachian State University, 1981)
In 1973, Cherokee students at the Qualla Boundary started a student organization with the intention of improving the educational prospects among Native Americans attending non-Indian colleges and universities. Under the direction of Laurence French and Charles Jim Hornbuckle, the students interviewed Cherokee elders and received help from the American Indian Historical Society in order to gain an accurate history and assessment of the tribe, which has a long misunderstood history. In order to gain more traction and involvement in the project, special college courses were offered at the Cherokee High School under the supervision of French and Hornbuckle. Published in 1981, The Cherokee Perspective is a compilation of the articles written in these courses.